Effect of organic compounds on cognac sensory profile - Mikhail N. Eliseev (Kemerovo State University, 2021)
Introduction. The present research featured the effect of carbonyls, phenols, furans, fatty alcohols, ethers, and other chemical compounds on the sensory properties of cognac distillates of different ages. The research objective was to identify additional criteria of sensory evaluation by measuring the effect of various compounds on perception intensity. Study objects and methods. The study featured cognac samples of different ages. The experiment involved standard methods, including high-performance liquid and gas chromatography and a mathematical analysis based on Microsoft software. Results and discussion. The content of fatty alcohols, ethers, and carbonyl compounds that formed as a result of fermentation demonstrated little change during the aging period in oak casks. A longer extraction increased the content of phenolic and furan compounds and sugars. The content of terpene compounds decreased due to their high lability. The study revealed the effect of organic compounds on taste descriptors. The article introduces multivariate equations that calculate the dependences of the descriptor intensity on the content of organic compounds. A correlation and regression analysis revealed that phenolic compounds had a significant effect on the taste formation of cognac samples, depending on the aging time. Conclusion. Organic compounds proved to affect the taste profiles of cognac samples of different ages, as well as sensory evaluation descriptors.